The relationship between individualism and collectivism towards collaborative learning among University Malaya student / Zarifah Zaaba - Zaaba, Zarifah (2013)
The purpose of this article describes about the relationship of individualism and collectivism towards collaborative learning among University Malaya students. This paper was correlational that shown how far the level of individualism and collectivism were applied in order to know the effectiveness towards collaborative learning. Individualism and collectivism were the practices that important to students developed their collaborative learning. Nevertheless, this paper was emphasizing only three variables which are individualism, collectivism and collaborative learning. Then, the individualism and collectivism was discussed about the different patterns of endorsement that related to individualism and collectivism on the individual level that was distributed within national contexts. This paper also focuses at students from IPT A which are University Malaya students. The data was gathered by using the questionnaire method that had answered by 100 of degree students from the University Malaya. The study finds that the level of individualism and collectivism towards collaborative learning among University Malaya students was higher. Then, the hypothesis was accepted where there have a significant relationship between individualism and collectivism towards collaborative learning among University Malaya students. Hence, based on finding, collaborative learning was totally influenced student in learning environment.